Finest hour Winston S. Churchill, 1939-1941 - Gilbert, Martin 1936-2015 (William Heinemann Ltd, 1983)
In this, the most important volume, Martin Gilbert probes beneath the surface of each of the crucial decisions in which Churchill was involved from the outbreak of war in September 1939 to the Japanese attack on Pearl Harbor in December 1941. He reveals not only how each decision was reached but precisely what influences lay behind it, pieced together from an even more diverse documentary history than earlier volumes: documents Churchill sent and received, the diaries and letters of his private secretaries, the recollections of those who worked with him, as well as the records from the War Cabinet and other Government agencies.